Fracasso escolar e relação com o saber: a educação mobilizadora em Bernard Charlot - Silva, Flávio Roberto Vieira da (2014)
Bibliographical research on the concept of relationship with knowledge as a theoretical basis for the formation of a sociology of the subject, which is articulated in the polls Bernard Charlot about school failure, whose theoretical and methodological point of departure requires overcoming the negative reading, that analysis in terms of lack of lack: lack of skills, lack of skills, lack of knowledge. This bias, the sociology of reproduction, by authors such as Pierre Bourdieu and Jean-Claude Passeron, statistically related to social background and school performance, which usually presents deficit among students of popular media. But this statistical correlation canot be analyzed in terms of cause. The school is not only a space of social differentiation. Realize, also called paradoxical success: poor children who get academic success and other wealthier strata who fail in school. Charlot is necessary for us to develop a positive reading failure and school success, surpassing the objectivism of sociology without a subject (reproductivism). The theory of the relationship to knowledge (and school) allows understanding, through appropriate qualitative methodologies, as students construct themselves as subjects from relationships of identity, meaning, expectations about life and future career. In the globalized and computerized world, the school is losing power and strength as a socializing institution, so that from the relationship with knowledge we can identify mobilizing processes in school and about school. However, it is observed that the proposed subject of sociology by Charlot as a kind of sociology of success and failure in school – or even as a proposal for a mobilizing education – canot raise claims of exclusivity in that branch of study. Other theoretical proposals such as the sociology of school experience François Dubet or sociology of the individual Bernard Lahire make important contributions to the new conditions and forms of intra- and extra-school socialization in diverse societies. What's common between these authors is a fixation with microsociology, which Charlot leads to neo-Marxism (as he defines himself), and Dubet Lahire and leads to a pluralistic and multifaceted eclecticism.